Metataxonomic Analysis of Grape Microbiota During Wine Fermentation Reveals the Distinction of Cyprus Regional terroirs - Kamilari, Eleni; Mina, Minas; Karallis, Christos; Tsaltas, Dimitrios (Frontiers in Microbiology, 2021)
Wine production in Cyprus has strong cultural ties with the island’s tradition, influencing local and foreign consumers’ preferences and contributing significantly to Cyprus’ economy. A key contributor to wine quality and sensorial characteristics development is the microbiota that colonizes grapes and performs alcoholic fermentation. Still, the microbial patterns of wines produced in different geographic regions (terroir) in Cyprus remain unknown. The present study investigated the microbial diversity of five terroirs in Cyprus, two from the PGI Lemesos region [Kyperounta (PDO Pitsilia) and Koilani (PDO Krasochoria)], and three from the PGI Pafos region [Kathikas (PDO Laona Akamas), Panayia, and Statos (PDO Panayia)], of two grape varieties, Xynisteri and Maratheftiko, using high-throughput amplicon sequencing. Through a longitudinal analysis, we examined the evolution of the bacterial and fungal diversity during spontaneous alcoholic fermentation. Both varieties were characterized by a progressive reduction in their fungal alpha diversity (Shannon index) throughout the process of fermentation. Additionally, the study revealed a distinct separation among different terroirs in total fungal community composition (beta-diversity) for the variety Xynisteri. Also, Kyperounta terroir had a distinct total fungal beta-diversity from the other terroirs for Maratheftiko. Similarly, a significant distinction was demonstrated in total bacterial diversity between the PGI Lemesos region and the PGI Pafos terroirs for grape juice of the variety Xynisteri. Pre-fermentation, the fungal diversity for Xynisteri and Maratheftiko was dominated by the genera Hanseniaspora, Aureobasidium, Erysiphe, Aspergillus, Stemphylium, Penicillium, Alternaria, Cladosporium, and Mycosphaerella. During and post-fermentation, the species Hanseniaspora nectarophila, Saccharomyces cerevisiae, Hanseniaspora guilliermondii, and Aureobasidium pullulans, became the predominant in most must samples. Regarding the bacterial diversity, Lactobacillus and Streptococcus were the predominant genera for both grape varieties in all stages of fermentation. During fermentation, an increase was observed in the relative abundance of some bacteria, such as Acetobacter, Gluconobacter, and Oenococcus oeni. Finally, the study revealed microbial biomarkers with statistically significant higher relative representation, associated with each geographic region and each grape variety, during the different stages of fermentation. The present study’s findings provide an additional linkage between the grape microbial community and the wine terroir.